Varying effects of climate change on the photosynthesis and calcification of crustose coralline algae: Implications for settlement of coral larvae - Jennifer M. Sneed; Justin E. Campbell; Audrey Looby; Aurora Giorgi; Valerie J. Paul (Climate Change Ecology)
Coral recruitment is critical to the maintenance of healthy coral reef ecosystems. Many coral species settle preferentially on certain crustose coralline algae (CCA) (e.g., Hydrolithon boergesenii) over others (e.g., Paragoniolithon solubile). Calcifying organisms like CCA are particularly susceptible to ocean acidification (OA), and settlement behavior of larvae may be compromised as seawater temperatures increase (ocean warming; OW) and pH levels decrease as a result of climate change. Here, we examine the effects of future seawater conditions (OW and OA) on the calcification and photosynthetic efficiency of two CCA species, H. boergesenii and Pa. solubile. We also examine the effects of conditioning CCA in combined OA and OW on the settlement preferences of three coral species, Acropora palmata, A. cervicornis and Porites astreoides. Acropora palmata and Po. astreoides demonstrated a preference for H. boergesenii over Pa. solubile in choice experiments after short-term treatment (7–21 days) and this preference was not affected by future seawater conditions. A. cervicornis did not demonstrate a CCA preference under any treatment. Po. astreoides did not demonstrate a CCA preference in no-choice assays and settlement was unaffected by OW and OA even after the longest exposure (99 days). Both CCA had reduced photosynthetic efficiency after exposure to future seawater conditions. However, net calcification rate was reduced in H. boergesenii but not Pa. solubile after exposure to future seawater conditions. These results demonstrate that while climate change may differentially affect the physiological functioning of various species of CCA, coral settlement preferences are unlikely to be altered.